Obstetrics nemesis or decrease in risk? A bioethical debate on interventionist treatments in low risk childbirths - Hernández Garre, José Manuel; Echevarría Pérez, Paloma; Gomariz Sandoval, María José (Acta Bioethica, 2017)
For decades in low-risk deliveries has been addressed, mainly in the clinical-hospital setting, from an interventionist perspective characterized by medicalization, mechanization and machining care. In this context the present study lies, whose aim was to explore the bioethical limitations of this interventionist paradigm of care through an analysis of its clinical pragmatism compared to other approaches more humanistic. For this it has conducted a thorough analysis of documents in different databases in the field of medical and social sciences, selecting both items of scientific diffusion as books, statements, strategies and clinical practice guidelines. The results show a medicalized care pattern appears to increase the iatrogenic effects in low-risk deliveries. We conclude that this is a culture of birth which, to some, it violates basic bioethical principles to subjugate the dignity of female corporeality to contingent economic interests and transhumanists, biopolitics and taylorist ideologies reifying.